Exploring the Future of FinTech with a Bachelor of Financial Technology degree at Universiti Malaysia Pahang Al-Sultan Abdullah - Irene, Wei Kiong Ting; Norwazli, Abdul Wahab (UMPSA, 2025)
The financial technology (FinTech) landscape is evolving at an unprecedented pace, driven by groundbreaking advancements in artificial intelligence, blockchain, big data, and digital finance. Globally, the FinTech market is projected to reach a value of USD 698.48 billion by 2030, growing at a compound annual growth rate (CAGR) of 20.3% from 2023 to 2030. This rapid growth underscores its transformative impact across multiple sectors, including banking, insurance, investment, and e-commerce.